STRATEGI KOMUNIKASI DIGITAL DALAM PEMASARAN: ANALISIS EFEKTIVITAS KAMPANYE DI PLATFORM SOSIAL MEDIA - Al-Amin; Nashran Azizan (Jurnal Komunikasi, 2025)
In today's digital era, the use of digital communication strategies in marketing, particularly through social media platforms, has become a key factor in creating and executing eflective campaigns. This research investigates the various aspects that determine the eflectiveness of digital communication strategies in marketing campaigns across various social media platforms. It highlights the importance of integrating a deep understanding of digital technology, careful data analysis, and creativity in the development of digital communication strategies, which not only increase awareness and engagement but also drive customer conversion and loyalty